Production of body fat in lactating ewes using the diameter of subcutaneous adipocyte cells or body condition score - Susmel P.; Canavese B.; Filacorda S.; Piasentier E. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
The relationship between cellular dimensions or body condition score and fatness was studied in 35 lactating Bergamasca ewes. Eleven animals (group 1) were slaughtered within 2 weeks of lambing and the remainder (group 2) within 6 or 7 weeks of lambing. The chemical body fat was determined by ether extract analysis of 5 minced fractions of the empty body (23 ewes) or estimated from the weights of empty body, body dry matter and dissected kidney and pelvic fat. The adipocyte diameter (D) was calculated from an average of 200 measurements by light microscopy of 200 microm cryostat sections, obtained from 1 g samples of subcutaneous adipose tissue taken from the rump, fixed in 35 per cent neutral formalin and frozen in liquid nitrogen. The body condition score (BS) was measured 1 hour before slaughter by two operators using a 1 to 5 score range with intervals of 0.25 units. The variation in the degree of fatness between the ewes at different stages of lactation was accompanied by changes in adipocyte dimensions and BS. A significant intra-group linear relationship among empty body fat content and both body condition measures was also observed. Intra-group and pooled correlation coefficients were higher with D than BS. The best prediction equation of body fat content (BF, g/Kg LW) was obtained with D2 (R2
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)